A family of compensation topologies for capacitive power transfer converters for wireless electric vehicle charger. (15th February 2020) - Li, Lantian; Wang, Zhenpo; Gao, Feng; Wang, Shuo; Deng, Junjun
Highlights: The capacitive power transfer is focused for electric vehicle charging application. A family of compensation topologies converters is presented. The compensation topologies are derived and categorized by output requirement. A design procedure is summarized to devise resonant networks and parameters. A tuning way is proposed for zero voltage switching with varied coupling capacitor. Abstract: A large scale of electric vehicles can ideally maintain the stability of renewable power supply by acting as storage buffers for alleviating the intermittence in the integration of renewable energy sources for constructing a low-carbon energy system. However, the inconvenient conductive charging becomes a barrier in the popularization of electric vehicles. Wireless power transfer technology is in the spotlight because of the flexibility and convenience in powering electric vehicles. Recently, the Capacitive Power Transfer has received extensive attention due to simple coupler structure, rotatable coupler, and negligible heating of the metal foreign object. In the capacitive-based wireless charging system, the higher-order compensation topology is essential to enhance power transfer capability limited by the small coupling capacitance. However, with the increase of the resonant elements, the form of the resonant network becomes diverse. Currently, the researches focus on the characteristics of specific symmetrical compensation topologies. This paper presents a family of compensation topologies for the Capacitive Power Transfer system to achieve constant-voltage or constant-current output. A design procedure is summarized to construct the resonant networks, so as to design the compensation parameters. Considering the coupling capacitor variations caused by parking position deviation, a parameter tuning method is proposed to realize primary zero-voltage switching by adjusting the parameter of the double-sided inductor-capacitor-inductor-capacitor compensation topology. Experiments show that the prototype achieves constant-current output and zero-voltage switching when the coupling capacitance varies. The system efficiency reaches 93.57% at 1.5 kW input power with the input and output voltage around 250 V.